What farmers want from mental health and wellbeing-focused websites and online interventions. (August 2021) - Gunn, Kate M.; Barrett, Alison; Hughes-Barton, Donna; Turnbull, Deborah; Short, Camille E.; Brumby, Susan; Skaczkowski, Gemma; Dollman, James
Abstract: Introduction: Farming is a physically and psychologically hazardous occupation and farmers face numerous attitudinal and structural barriers to accessing mainstream health and mental health services. As Internet access increases across rural Australia there is potential for online interventions to help overcome barriers and provide new avenues for improving farmers' mental health and wellbeing. However, little is known about how farmers perceive this approach which is problematic given the importance of building in their preferences, to ensure these interventions meet their interests and needs, and have maximum impact. The purpose of this study was to explore the scope of Australian farmers' current Internet use and their views and preferences on the design and delivery of online, mental health and wellbeing-focused interventions. Methods: Eighteen farmers (11 men and 7 women, with a median age of 45.5 years) from grain, sheep and/or cattle farms across four states of Australia participated. Telephone-based, semi-structured interviews were used to explore their current Internet use practices and preferences regarding new websites to promote farmers' mental health and wellbeing. Thematic Framework Analysis was used to analyze and organize the data. Results: Eight key topics were discussed and several themes within each topic emerged. The first topic related to farmers' current Internet use practices (found to be sporadic, used for weather, banking, emails and research, they are open to using it for health and wellbeing, and they reported that Twitter and other social media reduces social isolation). Themes demonstrating farmers' specific preferences on four aspects of web-design included; preferred aesthetics (authenticity, reflective of farmer diversity, simple layout and font, colours of nature, mix of cartoons and real-life, positive, masculine imagery); preferred language (lay, casual tone, careful use of humour, positive/empowering); preferred technical aspects/capabilities (unreliable Internet connections, limited downloads, compatibility with multiple devices, easy to use, inclusion of music problematic, mixed opinion about inclusion of scientific references and chat features, include videos, case studies) and preferred content/focus for websites of this type (early intervention/prevention, where and how to seek more help). More broadly, contextual influences to consider (multiple pressures of farm life, time poverty, farmers' outlook is practical and outcome-driven, stigma about mental health decreasing but still exists); strategies to promote engagement (must feel engaged, know what is next, see benefits quickly) and marketing/promotion suggestions (women as advocates for men, use trusted sources to promote, emphasize that information can be accessed from privacy of own home/farm) were also highlighted by participants. Conclusions: Findings will help inform the development of new mental health and wellbeing-focused online interventions for farmers to maximize uptake, engagement and impact. In particular, these interventions need to be perceived as relevant and authentic, while also reflecting the diversity of the farming population, which farmers believe can be achieved by carefully considering their preferences for aesthetics, language, technological requirements and the unique farming context. Highlights: Authentic, positive (e.g. not drought), masculine, farming-related imagery in the colours of nature (particually green) favoured. Videos, case studies, simple layouts and fonts preferred. Lay language that is casual, positive, empowering and carefully humorous valued. Ease of use, multiple device compatibility and the ability to operate with poor internet is important. Exposure to multiple pressures, lack of time, practical and outcome-driven nature and stigma concerns require consideration. There is a particular need for new online resources focusing on early intervention/prevention.